ANALISIS DETERMINAN PENDAPATAN PADA PEDAGANG DI PASAR DALEMAN KECAMATAN BAKI SUKOHARJO - Sepfiola Elisabet; Astuning Suharsini (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to find out that the income of Pasar Daleman traders, Baki Sukoharjo District, was affected by business capital, business location, length of business and application of accounting records during the pandemic. A total of 150 traders became the population in this study. Sampling by simple random sampling technique as many as 60 respondents. Questionnaires with a Likert scale were used for data collection. Data analysis used multiple linear regression techniques and quantitative data. Based on the research findings, it shows that partially or simultaneously business capital, business location, length of business and the application of accounting records have had a significant impact on the income of traders in Pasar Daleman, Baki Sukoharjo District during the pandemic